2017
DOI: 10.3390/vaccines5040041
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Micelle-Based Cytoplasmic Delivery System for Induction of Cellular Immunity

Abstract: (1) Background: Cytoplasmic delivery of antigens is crucial for the induction of cellular immunity, which is an important immune response for the treatment of cancer and infectious diseases. To date, fusogenic protein-incorporated liposomes and pH-responsive polymer-modified liposomes have been used to achieve cytoplasmic delivery of antigen via membrane rupture or fusion with endosomes. However, a more versatile cytoplasmic delivery system is desired for practical use. For this study, we developed pH-responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…42 Indeed, increased colocalization of OVA with MHC I exhibiting a diffuse cytosolic-like staining was observed in BMDCs cotreated with OVA plus βγ-CAT ( Figure 2D), and similar results has been reported that the cytoplasmic delivery of antigen may induce cross-presentation to activate antigenspecific cellular immunity. 43 Thus, our results suggested that βγ-CAT might induce the release of endocytic OVA into the cytoplasm to trigger the MHC I processing pathway via pore formation and neutralization of intracellular acidification. In addition, we further assessed the colocalization of OVA and MHC II in BMDCs treated with βγ-CAT.…”
Section: βγ-Cat Increases Antigen Presentation Capacity By Bmdcs VImentioning
confidence: 60%
“…42 Indeed, increased colocalization of OVA with MHC I exhibiting a diffuse cytosolic-like staining was observed in BMDCs cotreated with OVA plus βγ-CAT ( Figure 2D), and similar results has been reported that the cytoplasmic delivery of antigen may induce cross-presentation to activate antigenspecific cellular immunity. 43 Thus, our results suggested that βγ-CAT might induce the release of endocytic OVA into the cytoplasm to trigger the MHC I processing pathway via pore formation and neutralization of intracellular acidification. In addition, we further assessed the colocalization of OVA and MHC II in BMDCs treated with βγ-CAT.…”
Section: βγ-Cat Increases Antigen Presentation Capacity By Bmdcs VImentioning
confidence: 60%
“…More advanced strategies to facilitate immunogenic delivery into the cytosol depend on the lower pH of the early/late endosome . For example, CaP skeleton as a shell protects CpG oligonucleotides from clearance by macropinocytosis and responds to acidic organelle environment for on‐command release in cytosol .…”
Section: Nanomaterials For Target Deliverymentioning
confidence: 99%
“…[129] More advanced strategies to facilitate immunogenic delivery into the cytosol depend on the lower pH of the early/late endosome. [130][131][132][133][134] For example, CaP skeleton as a shell protects CpG oligonucleotides from clearance by macropinocytosis and responds to acidic organelle environment for on-command release in cytosol. [135] An alternative method involves cell-penetrating peptides on the nanoparticle surface, which Small 2019, 15,1900262 Reproduced with permission.…”
Section: Nanomaterials Promote Intracellular Delivery Of Immunotherapmentioning
confidence: 99%
“…[ 69 ] For example, PEG can be utilized as functional ligands to enhance the flexibility of dendrimers, so as to improve the efficiency of delivering genes to immune cells. [ 70 ] More interestingly, dendrimers can recognize DCs through multiple receptors (i.e., C‐type polylectin receptor CD205, mannose receptor (MR or CD206), dendritic cell‐specific intercellular adhesion molecule 3 grabbing nonintegrin or DC‐SIGN, as well as lectin 1/2) and further internalize DCs to promote further immune response ( Figure a). [ 71 ]…”
Section: Structural Designs Of Polymeric Nonviral Gene Delivery Systemsmentioning
confidence: 99%